KURIKULUM PENDIDIKAN MATEMATIKA PADA TINGKAT SEKOLAH MENENGAH (SECONDARY SCHOOL) DI INDONESIA DAN SINGAPURA - Siregar, Nur Fauziah (Koordinat Jurnal MIPA, 2024)
The curriculum is a set of designed arrangements that include goals, materials, methods, and assessments used in the educational process. The curriculum serves as a guide for implementing learning activities and functions as a tool to achieve the objectives of education. This study aims to compare the mathematics curriculum at the secondary school level in Indonesia and Singapore. This research is qualitative, using descriptive methods and data collection techniques from articles, journals, books, and online media. The results obtained indicate that the Indonesian curriculum emphasizes 21st-century competency achievements, while Singapore focuses primarily on problem-solving with five conceptual goals. The content of the secondary school mathematics curriculum in Indonesia consists of numbers, algebra, measurement, geometry, data analysis and probability, as well as calculus, whereas Singapore's curriculum includes numbers and algebra, geometry and measurement, and statistics and probability. Mathematics learning in Indonesia is project-based, reinforcing the Pancasila student profile. Meanwhile, in Singapore, the Singapore Math teaching method focuses on two main principles: the Concrete, Pictorial, Abstract (CPA) approach and mastery of content. The assessment methods used are both formative and summative but with different objectives